On Translating 2nd Person Pronoun (English and Indonesian) : A Case Study on BPPT Parallel Corpus - . Prihantoro (Bandar Lampung University (UBL), 2013)
Many linguists have posited a number of distinct types of translation method, but almost all agree on the existence of word-for-word translation, which to some extent must be avoided to generate natural translation in the target language. Some other methods are proposed to obtain natural translation but in this paper, we refer to communicative translation (Newmark, 1988). However, it does not suggest that some other methods such as faithful or word-for-word translation are useless. It is necessary that these methods apply to the whole text, as some items require faithful or word-for-word translation as well. However, these methods must be avoided when translating culture based item, e.g an entity that does not exist in the target language. On one hand, almost all languages make use of pronouns. On the other hand, the social dynamics of pronoun itself requires translators to shift from word-for-word translation method to another method as the culture polarity shift from source to target language. The data in this research is obtained from English-Indonesian Parallel Corpus by Indonesian Agency for the Assessment and Application of Technology (2008), which consists of written and spoken data. The result of this research suggests that some speaker-hearer relations cannot be fully expressed by English pronouns when translated to Indonesian. There are cases when culture based polarity requires pronoun to shift to proper name. Even when pronoun-to-pronoun translation is preserved, the paradigm changes: such as inclusive/exclusiveness which functions as in/out group identity marker.